THERAPEUTIC POTENTIAL OF DOXORUBICIN LOADED POLY (D, L-LACTICCO- GLYCOLIC ACID) AGAINST p- DIMETHYLAMINOAZOBENZENE INDUCED - KRISHNAMOORTHY LAKSHMI PRIYA; AROCKIAM ANTONY JOSEPH VELANGANNI (International Journal of Pharma and Bio Sciences, 2015)
The anticancer effect of doxorubicin loaded PLGA nanoparticles on p-Dimethylaminoazobenzene (p-DAB) induced liver cancer in male albino rats has been studied. Nanoparticles of poly (D, L-Lactic-co-glycolic acid) (PLGA) were developed by nanoprecipitation method as a delivery system for doxorubicin. Doxorubicin was chemically conjugated to a terminal end group of PLGA. Group I animals were fed with feed and water ad libitum and served as control. Group II-IV animals were received p-DAB intraperitoneal injection at 20mg/kg body weight once in a week for two months. Then group III animals received an intravenous injection of doxorubicin (240µg/kg body weight) in a tail vein daily. Group IV animals were received intravenous injection of PLGA nanoencapsulated doxorubicin (420µg of equivalent doxorubicin/kg body weight) in tail vein daily and stopped to the conclusion of the experiment. Doxorubicin loaded PLGA nanoparticles were characterized by X-ray diffractometer (XRD), Transmission Electron Microscopy (TEM) and Fourier Transmission Infra-Red microscopy (FTIR). The elevated levels of protein, SGOT, SGPT in the p-DAB administered group were significantly reduced by doxorubicin loaded PLGA nanoparticles than free doxorubicin. In vivo anticancer activity showed that administration of doxorubicin loaded PLGA nanoparticles had superior activity over free doxorubicin.